CntA oxygenase substrate profile comparison and oxygen dependency of TMA production in Providencia rettgeri. (7th November 2017) - Kalnins, Gints; Sevostjanovs, Eduards; Hartmane, Dace; Grinberga, Solveiga; Tars, Kaspars
Abstract : CntA oxygenase is a Rieske 2S‐2Fe cluster‐containing protein that has been previously described as able to produce trimethylamine (TMA) from carnitine, gamma‐butyrobetaine, glycine betaine, and in one case, choline. TMA found in humans is exclusively of bacterial origin, and its metabolite, trimethylamine oxide (TMAO), has been associated with atherosclerosis and heart and renal failure. We isolated four different Rieske oxygenases and determined that there are no significant differences in their substrate panels. All three had high activity toward carnitine/gamma‐butyrobetaine, medium activity toward glycine betaine, and very low activity toward choline. We tested the influence of low oxygen concentrations on TMA production in CntA‐containing Providencia rettgeri cell cultures and discovered that this process, although dependent on the amount of oxygen, is still feasible in environments with 1 and 0.2% oxygen, which is comparable to oxygen levels in some parts of the digestive system.